A Pairing Free Secure Identity-based Aggregate Signature Scheme Under Random Oracle - Abouelkheir, Eman; Tromp, Jolanda G. (Informatica, 2017)
The signature aggregation is efficient for the communication links as the time complexity is independent of n different users. The bilinear pairing requires super-singular elliptic curve groups that have a spacious range of elements. Also, the point multiplication over elliptic curve is less computational cost than the pairings, therefore, the pairing-based schemes expose more computational complexity than schemes that without pairings. This paper introduces a new efficient and secure pairing free signature scheme based on the idea of aggregation. Also, the proposed scheme without pairings offers lower computational cost than other schemes from pairings as it saves 68.69% from computations.